The Experiences Of Child Marriage Among Rohingya Refugee Girls In Malaysia: A Qualitative Analysis - Dee, Kaney Anita (2024)
The Rohingya, a Muslim ethnic group, have fled Myanmar for decades due to oppression, persecution, and being denied citizenship. Many Rohingya have fled to Malaysia because it is a Muslim country and offers low-skilled employment opportunities. Malaysia has not ratified the 1951 Refugee Convention and 1967 Protocol, hence the Rohingya in Malaysia are considered as illegals, denying them legal work and education in government schools. The Rohingyas’ status as stateless refugees and their patriarchal culture led to a high prevalence of child marriage among the Rohingya. This qualitative study explored the perspectives of the Rohingya on child marriage. It also examined factors associated with child marriage among the Rohingya in Malaysia. Finally, it explored solutions to prevent child marriage among the Rohingya. The researcher interviewed Rohingya women who married as girls (n=14). The researcher also conducted focus group discussions with community stakeholders (n=18) and Rohingya men aged 35 and older (n=20). Data were analysed and themes were identified using Atlas.ti software. Respondents shared a variety of perspectives about Rohingya child marriage, including that it is common, has some positive aspects, and cannot be stopped.